KAJIAN LIMBAH BUAH DAN SAYUR DENGAN ILMU AGROTEKNOLOGI SEBAGAI ENERGI ALTERNATIF BIO BATERAI - Andinata, Yoffi (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
A lot of decaying fruit and vegetable waste is seen at the vegetable and fruit market. The rotting fruit and vegetable waste experience a chemical process is known as fermentation. During this process, fruits and vegetables produce more acid which will increase the strength of the electrolytes inside fruit and vegetables. Thus, juices from old or rotten fruits and vegetables become is more reactive with the electrodes and produce a voltage that is higher than fresh fruit or vegetable juice. From the nature of the electricity that contains a lot  the electrolytes from the fruits and vegetable waste, the researchers aim to determine the strong value of the current and voltage generated by the bio-battery waste of citrus fruits, bananas, tomatoes, chilies, and carrots to make bio-batteries optimal. This research is carried out in several stages. The first stage to find out the influence of the distance between the electrodes on the strong current and voltage generated by a single bio-battery of fruit and vegetable waste. The distance between the electrodes used is 2 cm, 4 cm, 6 cm, 8 cm, and 10 cm using Cu electrodes as anode and Zn as a cathode. The area of ​​the electrode used (6 x 4) cm immersed in a bio-battery container with an electrolyte volume of 750 ml. The second stage to determine the strong value of current and voltage produced by serial bio-battery. The electrodes used were 6 Cu and Zn plates each with 6 bio-battery containers which will be arranged in series and measured strength current and voltage.